Aspidosperma discolor A. DC. SEEDLING GROWTH UNDER DIFFERENT SHADING LEVELS - Lima, Tarcísio Viana de; Feliciano, Ana Lícia Patriota; Marangon, Luiz Carlos; Araujo, Emmanoella Costa Guaraná; Silva, Thiago Cardoso; Chagas, Kyvia Pontes Teixeira das (Floresta, 2023)
This study aimed to evaluate the development of Aspidosperma discolor A. DC. seedlings two different origins subjected to full sunlight or different shading levels in a forest nursery, in addition to identifying its effective ecological group. Closed and pre-mature greenish-yellow colored follicles were collected from 10 randomly selected mother trees in two natural populations of lowland Dense Ombrophilous Forest fragments, both in Pernambuco, Brazil. The seedlings of these seeds were developed under different shading levels. After the seedlings were developed, the following variables were evaluated: number of leaves, leaf area and dry biomass. The species showed favorable phenotypic plasticity for its acclimatization in environments with moderate to intermediate shading conditions, a characteristic evidenced in small gaps; as well as for dense conditions, typical of vegetation with a closed canopy. A shading level of 50% stood out to produce A. discolor seedlings in a forest nursery, as it favors greater growth and biomass of the shoot and root parts. In addition, it presents peculiar ecological behavior of facultative sciophilous taxa or intermediate succession stages.